Don´T Cheat Like I Did: Possessive Jealousy and Infidelity in Close Relationships - Fernandez-Tapia, A (PsychOpen, 2020)
In a sample of 68 adult men and 70 adult women from Santiago, Chile, with a mean age of 29.40 years and a median age of 29, the effects of one s own infidelity and that of one s partner on different types of jealousy were examined. Of the respondents 47.1% had ever been unfaithful, and over half (56.5%) reported that their partner had been unfaithful. There were no effects of one s own infidelity and that of one s partner on reactive and anxious jealousy, but those who had been unfaithful, as well as those whose partner had been unfaithful, expressed the highest levels of possessive jealousy. These effects were not moderated by gender nor did age affect jealousy. Women were higher in all types of jealousy than men were. © 2020, PsychOpen. All rights reserved.